Eukaryotic-Type Ser/Thr Protein Kinase Mediated Phosphorylation of Mycobacterial Phosphodiesterase Affects its Localization to the Cell Wall - Malhotra, Neha; Chakraborti, Pradip K. (Frontiers in Microbiology, 2016)
Phosphodiesterase enzymes, involved in cAMP hydrolysis reaction, are present throughout phylogeny and their phosphorylation mediated regulation remains elusive in prokaryotes. In this context, we focused on this enzyme from Mycobacterium tuberculosis. The gene encoded by Rv0805 was PCR amplified and expressed as a histidine-tagged protein (mPDE) utilizing Escherichia coli based expression system. In kinase assays, upon incubation with mycobacterial Clade I eukaryotic-type Ser/Thr kinases (PknA, PknB and PknL), Ni-NTA purified mPDE protein exhibited transphosphorylation ability albeit with varying degree. When mPDE was co-expressed one at a time with these kinases in E. coli, it was also recognized by an anti-phosphothreonine antibody, which further indicates its phosphorylating ability. Mass spectrometric analysis identified Thr-309 of mPDE as a phosphosite. In concordance with this observation, anti-phosphothreonine antibody marginally recognized mPDE-T309A mutant protein; however, such alteration did not affect the enzymatic activity. Interestingly, mPDE expressed in Mycobacterium smegmatis yielded a phosphorylated protein that preferentially localized to cell wall. In contrast, mPDE-T309A, the phosphoablative variant of mPDE, did not show such behaviour. On the other hand, phosphomimics of mPDE (T309D or T309E), exhibited similar cell wall anchorage as was observed with the wild-type. Thus, our results provide credence to the fact that eukaryotic-type Ser/Thr kinase mediated phosphorylation of mPDE renders negative charge to the protein, promoting its localization on cell wall. Furthermore, multiple sequence alignment revealed that Thr-309 is conserved among mPDE orthologs of M. tuberculosis complex, which presumably emphasizes evolutionary significance of phosphorylation at this residue.